Contemporary German geopolitics – continuity and change (Economic and Political Thought, 2016)
German geopolitics is burdened with “original sin” – when in the years1933–1945 it was used for the policy of conquests, it justified mass war crimescommitted by the Third Reich. That is why after World War II the mainassumptions of German geopolitics were discredited and discontinued. Contemporarydiscussion on German geopolitics is mainly based on the consequencesof the central location of Germany in Europe. Elements of geopoliticscan be found in the role of Germany as an intermediary between Russiaand the West, special treatment of Russia and solving the migration crisis. Itrevealed new divisions between Eastern Europe and Western Europe, whichrefer to the old visions of geopolitical interests of national states.